CYP2C19 genotype-guided escalation to ticagrelor vs. clopidogrel in secondary stroke prevention: a retrospective cohort study - Haidong, Sun; Min, Deng; Hong, Yu; Jing, Yang (Frontiers in Pharmacology, 2026)
ObjectiveTo evaluate the effectiveness and safety of an antiplatelet therapy strategy guided by CYP2C19 genotyping in the secondary prevention of ischemic stroke in a real-world setting.MethodsThis single-center retrospective cohort study enrolled 623 ischemic stroke patients. Based on their CYP2C19 genotype (extensive metabolizer [EM], intermediate metabolizer [IM], poor metabolizer [PM]) and the actual P2Y12 receptor antagonist treatment received (clopidogrel or ticagrelor), patients were categorized into natural cohorts. To minimize confounding, we applied propensity score matching, yielding a final analysis cohort of 514 patients. The primary outcome was the incidence of major adverse cardiovascular events (MACE), including stroke recurrence, myocardial infarction, and cardiovascular death, within 12 months. The secondary outcome was bleeding events.ResultsWith respect to platelet reactivity, the proportions of high platelet reactivity in PM and IM patients (61.25%, 34.07%) were significantly higher than in EM patients (12.50%) (all P < 0.01). Regarding clinical efficacy, among PM and IM patients, the incidence of MACE was significantly lower in the ticagrelor group than in the clopidogrel group (10.00% vs. 30.00%, P = 0.025; 11.50% vs. 22.12%, P = 0.033, respectively). Among EM patients, there was no significant difference in MACE incidence between the two groups (5.77% vs. 6.73%, P = 0.928). After adjustment using Cox regression analysis, ticagrelor therapy emerged as an independent factor associated with a reduced risk of MACE in both PM (HR = 0.32, 95% CI: 0.11–0.89, P = 0.029) and IM (HR = 0.52, 95% CI: 0.28–0.98, P = 0.043) patients. Furthermore, there were no statistically significant differences in bleeding event rates between the two treatment strategies within any metabolic phenotype (all P > 0.05).ConclusionAntiplatelet therapy guided by CYP2C19 genotyping is an effective strategy for optimizing the secondary prevention of ischemic stroke. For IM and PM patients, switching from clopidogrel to ticagrelor significantly reduces the risk of recurrent ischemic events without increasing bleeding risk. In contrast, for EM patients, clopidogrel remained an effective and safe option.